Hydrological and Environmental Problems in Ethiopian River Basins: A Critical Review - Ilmi, Abu Dedo (Journal of Sustainable Infrastructure, 2025)
The river basins of Ethiopia are fundamentally important to the nation's hydrological resources concerning agriculture, energy production, and ecosystems. However, the basins face major hydrological and environmental problems associated with water scarcity, pollution, sedimentation, and the consequences of climate variability. The following critical review examines the hydrological and environmental problems of Ethiopian river basins, underlining the interlinkages between human activities, natural processes, and policy frameworks. It identifies the most important drivers of degradation and potential mitigation strategies, including integrated watershed management, sustainable land use practices, and improved governance. Addressing these challenges using evidence-based approaches will contribute to the resilience and sustainability of river basins in Ethiopia for national development and ecological health